2000
DOI: 10.1152/jappl.2000.89.3.996
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of respiratory motor output by cerebellar deep nuclei in the rat

Abstract: The present study was undertaken to determine what roles the various cerebellar deep nuclei (CDN) play in modulation of respiration, especially during chemical challenges. Experiments were carried out in 12 anesthetized, tracheotomized, paralyzed, and ventilated rats. The integrated phrenic nerve activity (integralPN) was recorded as an index of respiratory motor output. A stimulating electrode was sequentially placed into the fastigial nucleus (FN), the interposed nucleus, and the lateral nucleus. Only stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 27 publications
12
62
0
Order By: Relevance
“…Humans imagining exercise under hypnosis demonstrate a bilateral activation of the cerebellum in the area of the cerebellar fastigial nucleus (CFN) (522). Other studies have shown that there are projections from the CFN to medullary respiratory nuclei in addition to respiratory-modulated and chemosensitive neurons in the CFN (33,578,579,580). The modest attenuation of exercise hypocapnia during exercise in CFN-lesioned goats suggests that the CFN is part of the control system that enables the ventilatory response to meet the gas exchange requirements of submaximal exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Humans imagining exercise under hypnosis demonstrate a bilateral activation of the cerebellum in the area of the cerebellar fastigial nucleus (CFN) (522). Other studies have shown that there are projections from the CFN to medullary respiratory nuclei in addition to respiratory-modulated and chemosensitive neurons in the CFN (33,578,579,580). The modest attenuation of exercise hypocapnia during exercise in CFN-lesioned goats suggests that the CFN is part of the control system that enables the ventilatory response to meet the gas exchange requirements of submaximal exercise.…”
Section: Discussionmentioning
confidence: 99%
“…We observed in fact in 34% of the SIUDS/SIDS cases, developmental alterations of all these structures. Furthermore, likewise to PCs, also the inferior olivary nucleus and the dentate nucleus may play a critical role in modulating the respiratory pattern [17,33,38,44].…”
mentioning
confidence: 99%
“…Bassal and Bianchi (3) first reported an altered respiratory response to electrical stimulation of the FNr in cats. Subsequent studies confirmed that low-frequency electrical (3,22,23,43,46) or chemical activation (44) of FNr neurons predominantly elevated ventilation, often associated with a pressor response in both anesthetized cats and rats. Ablation of this region attenuated the respiratory response to severe hypercapnia and hypoxia (44,45).…”
Section: Nl N-methyl-d-aspartate) Stimulation Of the Vioc Augmented Vmentioning
confidence: 84%